Resolvin D1/N-formyl peptide receptor 2 ameliorates paclitaxel-induced neuropathic pain through the activation of IL-10/Nrf2/HO-1 pathway in mice - Su, Cun-Jin; Zhang, Jiang-Tao; Zhao, Feng-Lun; Xu, De-Lai; Pan, Jie; Liu, Tong (Frontiers in Immunology, 2023)
Paclitaxel (PTX) is a commonly used chemotherapy drug, but paclitaxel-induced neuropathic pain (PIPNP) is a common dose-limiting side effect. Resolvin D1 (RvD1) has been shown potent potency in promoting the solution of inflammation and chronic pain. In this study, we evaluated the effects of RvD1 on PIPNP and its underlying mechanisms in mice. The expression of 12/15-Lox, the RvD1 endogenous synthase, decreased in sciatic nerve and dorsal root ganglion (DRG) in PIPNP mice. Intraperitoneal (i.p.) injection of RvD1 promoted pain resolution of PIPNP. Intrathecal (i.t.) injection of PTX-treated bone-marrow-derived macrophage (BMDMs) sufficiently induced mechanical pain hypersensitivity in naïve mice, while pretreatment of RvD1 in BMDMs prevented it. Macrophage infiltration increased in the DRGs of PIPNP mice, but it was not affected by RvD1 treatment. RvD1 increased IL-10 expression in the DRGs and macrophages, while IL-10 neutralizing antibody abolished the analgesic effect of RvD1 on PIPNP. The effects of RvD1 in promoting IL-10 production were also inhibited by N-formyl peptide receptor 2 (FPR2) antagonist. The primary cultured DRG neurons apoptosis increased after stimulation with condition medium of PTX-treated BMDMs, but decreased after pretreatment with RvD1 in BMDMs. Finally, Nrf2-HO1 signaling was additionally activated in DRG neurons after stimulation with condition medium of RvD1+PTX-treated BMDMs, but these effects were abolished by FPR2 blocker or IL-10 neutralizing antibody. Our findings suggest that RvD1/FPR2 upregulates IL-10 in macrophages under PIPNP condition, and then IL-10 activates the Nrf2-HO1 pathway in DRG neurons, relieve neuronal damage and PIPNP. Thus, RvD1 may be a potential therapeutic strategy for clinical treatment of PIPNP.